Advancement in the mesothelioma diagnostics in Primorsko-Goranska County of Croatia - Lalić, Hrvoje, liječnik, 1960- (Array, 2009)
Abstract: The purpose is to find out whether the diagnostics and registration of patients with mesothelioma in the Littoral – Mountainous County of Croatia corresponds to the world trends. Further, the intention was to show the incidence of the disease and suggest the measures of prevention in the county of 400.000 inhabitants and its center Rijeka with 140.000 people. To that purpose 43 patients with mesothelioma were monitored in two groups: 25 shipyard workers, mean age 66, and 18 workers in other occupations, mean age 62. Statistically the group did not differ significantly in the incidence of placks, left or right side effusion. The pleural puncture showed the significance (p<0.05) for incidence of rouse cells. In 20 patients out of 43 mesothelioma was confirmed by taking the material for pathohistology by means of VATS (video assisted thoracoscopy) and in 14 patients by TTB (transthoracic biopsy) with CT control. Spirometric values showed moderate restrictive difficulties. Although a considerable improvement in diagnosing mesothelioma has been achieved in the last five years an improved prevention activity by occupational medicine is required not only by periodic checkups of the exposed persons and examinations for retired workers with respiratory difficulties, but also by stimulating work case histories